ONCOPLASTIC SURGERY IN CONSERVATIVE SURGICAL TREATMENT OF LOCALLY ADVANCED BREAST CANCER: A SYSTEMATIC REVIEW - Ribeiro, Daniela Cristina Camarotti Camara Escorel; Góes, Cláudia Almeida de Araújo; Andrade, Naiana Sacramento Couto; Ramos, Lucas Geovane; Ribeiro, Luiz Fernando Jubé; Paulinelli, Régis Resende (Mastology, 2018)
Introduction: Breast cancer conservative surgical treatment has become standard procedure as it reduces mutilation and preserves the body self-image. Advances in adjuvancy have increased its indications for larger tumors, and recent studies have been demonstrating its safety in locally advanced cases. Objective: To evaluate the role of oncoplastic surgery in the conservative surgical treatment of locally advanced breast cancer. Method: This is a systematic review. Out of the 523 studies found in the PubMed electronic database published between 2012 and 2017 using the keywords “breast cancer” and “oncoplastic surgery”, we selected 12 that dealt specifically with the topic. Results: No randomized trial was found. Most series were retrospective. The average initial tumor size ranged between 40 and 67.0 mm. The conversion rate from mastectomy to conservative treatment varied from 34 to 72.3%. Wise pattern was the most used technique. Oncoplastic surgery produced a greater amount of excised breast tissue. The oncoplastic technique did not differ from the standard conservative treatment concerning positive margins. Oncoplastic techniques showed higher rates of surgical complications but did not delay adjuvancy. Locoregional recurrence and overall survival ranged from 0 to 14.6% and 76.7 to 86.6%, respectively. Patients considered the cosmetic results acceptable in 84 to 92.3% of the cases. Conclusion: Oncoplastic surgical techniques allow a higher rate of breast conservation in locally advanced cancer, without apparent compromise of oncological safety.